2015
DOI: 10.5194/os-11-667-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale variability in the Arabian Sea from HYCOM model results and observations: impact on the Persian Gulf Water path

Abstract: Abstract. The Arabian Sea and Sea of Oman circulation and water masses, subject to monsoon forcing, reveal a strong seasonal variability and intense mesoscale features. We describe and analyze this variability and these features, using both meteorological data (from ECMWF reanalyses), in situ observations (from the ARGO float program and the GDEM -Generalized Digital Environmental mode -climatology), satellite altimetry (from AVISO) and a regional simulation with a primitive equation model (HYCOM -the Hybrid C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…5). This more dilute PGW is well marked in the blue profile; it a priori originated from the outflow during a previous season, and must have recirculated at the western end of the Sea of Oman, as observed in a numerical simulation (L'Hégaret et al, 2015). The coastal outflow of PGW appears on the brown and red profiles (upper panels of Fig.…”
Section: Sea Of Omansupporting
confidence: 54%
See 4 more Smart Citations
“…5). This more dilute PGW is well marked in the blue profile; it a priori originated from the outflow during a previous season, and must have recirculated at the western end of the Sea of Oman, as observed in a numerical simulation (L'Hégaret et al, 2015). The coastal outflow of PGW appears on the brown and red profiles (upper panels of Fig.…”
Section: Sea Of Omansupporting
confidence: 54%
“…During other seasons, the path of the PGW in the Gulf of Oman is less regular, as shown by observations and by numerical modeling; also, PGW can exit in the form of short pulses (see Banse, 1997;Senjyu et al, 1998;Bower et al, 2000;Prasad et al, 2001;Thoppil and Hogan, 2009;Wang et al, 2012;Wang et al, 2013). Recently, ARGO floats (see Carton et al, 2012;L'Hégaret et al, 2013) and HYCOM numerical simulations (see L'Hégaret et al, 2015) confirmed that during other seasons, PGW can be expelled from the coast into the Sea of Oman. These ejections were related to the presence of mesoscale eddies in the Sea of Oman, and especially to the presence of a dipole in spring; different offshore ejection mechanisms were identified.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations